Design and validation of a model for evaluating the quality of agricultural technical assistance in Colombia - Castaño-Reyes, Gulnara; Parrado-Barbosa, Álvaro; Molina-Ochoa, Juan Patricio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Technical assistance programs for agriculture in Colombia are regulated by laws, agreements, and policies that define the importance of evaluating and monitoring this service. National, regional and municipal entities are responsible for developing performance evaluations; however, several weaknesses are evident. This paper proposes the Quality Assessment Model of Agricultural Advisory Services (known in Spanish as MECATA), an evaluation tool based on the adaptation of an EFQM model (European Foundation for Quality Management). The MECATA model was developed from the selection of 39 variables related to service quality; this model considered the adjustment of three assessment tools and a validation process of two entities in Boyacá. The results showed a positive service assessment given by users and technical assistants, but lower qualifications were considered in variables such as process innovation, integral service, continued education, participation in other activities and market inclusion. MECATA proposes a quality assessment that integrates several perspectives of technical assistance services based on local community requirements; these results can be used as the basis for proposals for improvement.